Unsecured Microcredit and Small Medium Enterprise Empowerment: Evidence from Rural Indonesia - Liansi Liansi; Nani Hamdani Amir (Dinamis : Journal of Islamic Management and Bussiness, 2025)
This thesis discusses the impact of unsecured People's Business Credit (KUR) on the empowerment of Micro, Small, and Medium Enterprises (MSMEs) in Malimbu Village, Sabbang District. The research aims to determine the impact of unsecured KUR on the growth and development of MSMEs in Malimbu Village. It also aims to assess the changes in income and welfare of the community after receiving unsecured KUR, as well as to evaluate the sustainability of MSMEs in utilizing unsecured KUR for business development in Malimbu Village. The type of research used is descriptive qualitative research. The data sources are obtained from primary and secondary data through observation and interviews. The research instruments or tools used to collect data in this study include mobile phones, cameras, and interview guidelines. The data analysis techniques employed are data reduction, data presentation, verification, and conclusion. The results of this research show that: first. Providing People's Business Credit (KUR) without collateral in Malimbu Village has had a significant positive impact on the growth and development of Micro, Small and Medium Enterprises (MSMEs). second. Based on research results, this program has proven effective in increasing the income of MSMEs, improving the quality of education, and facilitating access to health services. THIRD. Based on the research results, the level of sustainability of MSMEs in utilizing KUR without collateral for business development in Malimbu Village can be considered good. Keywords : People's Business Credit, empowerment of MSMes.